2019
DOI: 10.15678/eber.2019.070303
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Knowledge Management Processes for the Creation of Competitive Advantage by Companies of Varying Size

Abstract: Praca została przygotowana w ramach projektu sfinansowanego ze środków Narodowego Centrum Nauki przyznanych na podstawie decyzji numer DEC-2011/03/N/HS4/00429, uzyskanych w ramach konkursu Preludium 2. Tytuł projektu: "Rola orientacji na wiedzę w procesie kształtowania przewagi konkurencyjnej przedsiębiorstwa w procesie internacjonalizacji", okres realizacji: 08.2012-08.2014r. Autor niniejszej rozprawy pełnił funkcję kierownika projektu, zaś funkcję promotora pełnił prof. dr hab. Krzysztof Fonfara, prof. zw. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…This conceptualization of MO was adopted in this research. Knowledge is one of the key assets that needs to be properly managed (Soniewicki & Paliszkiewicz, 2019). By empowering, disseminating, and using customer and market information, MO enables enterprises to tailor their activities to target markets, anticipate and respond to customer needs, as well as build competitive advantage (Atuahene-Gima, Slater, & Olson, 2005).…”
Section: Conceptualization Of Market Orientation In Literaturementioning
confidence: 99%
“…This conceptualization of MO was adopted in this research. Knowledge is one of the key assets that needs to be properly managed (Soniewicki & Paliszkiewicz, 2019). By empowering, disseminating, and using customer and market information, MO enables enterprises to tailor their activities to target markets, anticipate and respond to customer needs, as well as build competitive advantage (Atuahene-Gima, Slater, & Olson, 2005).…”
Section: Conceptualization Of Market Orientation In Literaturementioning
confidence: 99%
“…According to our results, competitor orientation significantly influences competitiveness and market performance as well. Soniewicki and Paliszkiewicz (2019) discovered that firms with more intensive knowledge management processes can achieve higher levels of competitiveness, while Wijaya and Suasih (2020) found that through competitive advantage, knowledge management has a significant positive effect on business performance as well. Although we did not investigate deeper the applied knowledge management practices, one part of the interfunctional coordination factor focused on how much the company uses tool(s) for knowledge sharing, which definitely is an element of knowledge management practices or processes.…”
Section: Resultsmentioning
confidence: 99%
“…Kankanhalli et al have recommended that companies should endeavour to strengthen their knowledge by establishing knowledge repositories. In addition, Soniewicki and Paliszkiewicz (2019) affirm that knowledge management procedures and policies are critical for big corporations in order for them to maintain competitiveness and that they require a robust development and financial support.…”
Section: Knowledge Management Capabilitiesmentioning
confidence: 96%
“…This affirms the findings by Tianrong (2016) who established that knowledge management is predominant in expedition of an organization's innovative capacity and competitive superiority. In addition, Soniewicki and Paliszkiewicz (2019) admit despite the size of the firm, the level of an organization's competitiveness increases just as it level of knowledge management procedures increased. On the percentage of universities that gave a negative response, this can be attributed to findings by who found that application of knowledge is limited if firms do not put in place effective systems of managing knowledge.…”
Section: Knowledge Management Capabilitiesmentioning
confidence: 99%